Chapter Chemical composition of microplastics floating on the Mediterranean Sea surface - Kedzierski, Mikaël (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Main objective of this study was to describe chemical composition of MP collected in surface waters of Mediterranean Sea. Samples were collected by manta net during Tara Mediterranean expedition (June-Nov.2014). Our results pointed to certain homogeneity at Mediterranean Sea scale. Main polymers collected were polyethylene (PE) (67.3±2.4%), polypropylene (20.8±2.1%), polystyrene (3.0±0.9%). Still, discrepancies, confirmed by literature, were observed at mesoscale level. Thus, in North Tyrrhenian Sea, proportion of PE was significantly lower than average value of Mediterranean Sea (57.9±10.5%).